Analysis and Design, Development of Auto Engage and Disengagement of Single Plate Clutches In Automatic Transmission System - Poonam P. Gawande; Varsha S. Patil; Darshana Harish Ghaware; Akanksha Arvind Pawar; Jyoti Gopal Jadhav (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The clutch plays a crucial role in the engagement and disengagement processes within the transmission system, facilitating the transfer of torque and power from the driving shaft to the driven shaft. Traditional transmission systems typically utilize a single plate clutch in conjunction with a manual transmission gearbox. The process involves three key operations: disengaging the clutch, changing gears, and gradually re-engaging the clutch when shifting from one gear to another. The operational principle of this clutch is based on that of a standard friction plate clutch, which includes friction and pressure plates along with springs; however, it eliminates the need for a foot pedal, thereby reducing the human effort required for clutch operation. The auto-disengagement single plate automatic clutch utilizes a single set of compression springs rather than the conventional two sets, allowing for a reduction in the weight of the centrifugal components. When the clutch is disengaged and the engine is idling, the hinged bob-weights rest against the lower or inward sides of the holes in the flywheel. The upward movement of these bob weights is responsible for engaging the clutch, thereby enabling the transmission of torque and power to the driven shaft.
Keywords: Clutch; Engagement; Gear; Transmission; Power; Shaft; Torque